Cloning and expression analysis of allograft inflammatory factor type 1 in coelomocytes of antarctic sea urchin (Sterechinus neumayeri) - Ovando, Fernanda; Gimpel, Carla; Cardenas, Constanza; Machado Cunha Da Silva, Jose Roberto; De Lorgeril, Julien; Gonzalez, Marcelo (Journal of Shellfish Research, 2012)
We have cloned and characterized for the first time an allograft inflammatory factor 1 (Sn-AIF-1) from the Antarctic sea urchin. We report the cloning of Sn-AIF-1 cDNA and the characterization of its expression in coelomocytes after a bacterial challenge. The cDNA Sn-AIF-1 has a size of 608 bp and encodes a polypeptide of 151 aa. The deduced amino acid sequence has a putative size of 17.430 Da, an isoelectric point of 4.92, and shows 2 elongation factor handlike motifs that normally bind calcium ions. BLAST analysis revealed close matches with other known AIF-1. The deduced amino acid sequence of Sn-AIF-1 showed high homology with AIF-1 in vertebrates such as fish, mice, and humans; and in the case of invertebrates, the major degree of identity (55%) was with a predicted sequence of the purple sea urchin AIF-1, and 52% corresponded to a sponge. Expression of Sn-AIF-1 mRNA was analyzed by qPCR. Sn-AIF-1 mRNA expression was measured from coelomocytes after a bacterial challenge using RT-PCR and revealed that the gene was upregulated after 24 h. Sn-AIF-1 could participate in the inflammatory response, particularly in the activation of coelomocytes and their survival.